Mitigation of Cyanobacteria Isolated from Tri An Reservoir Using Local Soils - Luu, Pham Thanh; Yen, Tran Thi Hoang; Thuy, Hoang Thi Thanh; Loan, Tu Thi Cam (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 3DO - 10.25073/2588-1140/vnunst.5199, 2022)
Cyanobacterial blooms in eutrophic waters pose serious threats to public health, water quality, and ecological management worldwide. Mitigation of the problem is essential to maintain stainable development. In this study, the effectiveness of local soils collected from the Tri An Reservoir (TAR) lakeside in the removal of cyanobacteria Microcystis aeruginosa was investigated. The organic matter content and clay mineral were characterized and used for the experiment. Cell density, percentage of growth inhibition, and changes in cell morphology were observed and used at endpoints of the experiment. The three soil samples named TA1, TA2, and TA3 were characterized with a high proportion of illit, montmorillonit, and kaolinite, respectively. Our results indicated that different soil compositions generated different inhibition on the growth of M. aeruginosa . Exposure to the soil high in kaolinite (52.1%) at a dose of 500 mg/L completely inhibited M. Aeruginosa growth, while the soil contained a high amount of montmorillonit (42.3%) inhibited only 38.4% of the growth of M. aeruginosa . The half-maximal effective concentration (EC 50 ) values of the TA1, TA2, and TA3 soil samples were 351.6 mg/L, 668.9 mg/L, 201.3 mg/L, respectively. Our results suggested that soil rich in kaolinite can be used to prevent harmful cyanobacterial blooms in inland waters.